An Afghan graduate student's perception of elementary school social studies in Afghanistan and the Philippines, and their implications - Katawazi, Ghulam Qader 1947- (1978)
The main problem of this study was to determine and describe the perceptions of an Afghan Graduate student of elementary school social studies in Afghanistan and the Philippines. The method of research used in this study was a descriptive analysis of the researcher's experiences as a student and a teacher in Afghanistan and as a graduate student of the University of the Philippines. The perceptions of the researcher include that teachers in Afghanistan are less qualified compared with teachers in the Philippines, and that the majority of teachers in Afghanistan are males and most are not familiar with other methods of teaching.